HUBUNGAN ANTARA MOTIVASI KERJA, DISIPLIN KERJA DAN PENGETAHUAN KEPEMIMPINAN PENDIDIKAN DENGAN KINERJA KEPALA SEKOLAH - E Syarifudin (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2009)
The objectives of the research are to study the relationships between work motivation, Work discipline and knowledge about educational leadership with school principal's performance. This research was conducted at State Junior High School (SLTPN) Serang Regency, Banten Province with a sample of 60 selected randomly.The research reveals that there is positive correlation between: (1) work motivation and school principal's performance; (2) work discipline and school principal's performance; (3) knowledge about educational leadership and school principal's performance. Furthermore, there are positif correlation among work motivation, work discipline and knowledge about educational leadership with school principal's performance. Therefore, school principal's performance could be improved principal's performance. Therefore, school principal's performance could be improved by increasing work motivation, work discipline and knowledge about educational leadership.